A lithium-rich positive electrode material and its preparation method and application
Mo atoms were deposited on Li[Ni-Co-Mn]O2 positive electrode material through co-deposition method and ALD process, and doping systems and cladding layers were formed with polyethylene glycol and other substances, which solved the problem of insufficient cyclic and electrochemical performance of the positive electrode material, and achieved significant improvement in rate performance and cyclic performance.
Patent Information
- Application Number
- CN202411766876.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The positive electrode material of Li[Ni-Co-Mn]O2 lithium-ion battery has shortcomings in cycling performance, cation mixing, thermodynamic stability and side reactions, which affects its electrochemical performance.
The preparation method of the covered-modified composite ternary positive electrode material is adopted to prepare the ternary positive electrode material by co-deposition method, and Mo atoms are deposited on the WO3 substrate through the ALD process, and the intermediate liquid is prepared by combining polyethylene glycol, alkyl quaternary ammonium base, dimethyl sulfoxide and cellulose to form a doping system and a cladding layer to improve the structural stability and electrochemical properties of the material.
It significantly improves the rate performance and cycling performance of the positive electrode material, reduces the impedance of the battery, enhances the oxygen vacancy effect, ensures the return of lithium ions, and further improves the electrochemical performance.
Smart Images

Figure CN119240807B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of positive electrode materials, and more specifically, to a lithium-rich positive electrode material and a preparation method and application thereof. Background Art
[0002] The ternary layered structure of Li[Ni-Co-Mn]O2 lithium-ion battery cathode material has the advantages of high discharge capacity, good safety performance and low toxicity, and has become a hot topic for technicians to study. It is the development trend of lithium-ion battery cathode materials for high energy density hybrid vehicles.
[0003] Although the discharge capacity of Li[Ni-Co-Mn]O2 lithium-ion battery cathode material is very high, its cycle performance is poor, especially the charge and discharge performance at high charge cut-off voltage and high rate needs to be further improved. In addition, during the application process, Li[Ni-Co-Mn]O2 ternary material still has the following problems: 1. The mixed arrangement of cations in the lithium layer leads to a decrease in the initial charge and discharge efficiency; 2. The thermodynamic stability of the layered compound of the material after delithiation is poor, and it is easy to lose oxygen and phase change; 3. In a wide range of discharge voltage, it is easy to cause strong side reactions between the organic electrolyte and the electrode material, which increases the impedance of the battery during the charge and discharge process, thereby reducing the electrochemical performance of the material.
[0004] To address the current problems of Li[Ni-Co-Mn]O2 ternary materials, a more effective method is to carry out surface coating modification, which currently mainly includes carbon coating and oxide coating. Carbon coating is the process of using a carbon source to generate carbon through high-temperature cracking and evenly coating the material surface, which can reduce the charge transfer resistance of the positive electrode material during the charging and discharging process; oxide coating is the process of modifying the surface of the positive electrode material with oxides, maintaining the positive electrode active material's own high initial capacity, preventing the dissolution of metal ions in the electrolyte, and inhibiting the occurrence of side reactions, thereby improving the capacity retention rate of the positive electrode material.
[0005] The above-mentioned coating modification methods have improved the cycle performance of Li[Ni-Co-Mn]O2 ternary materials to a certain extent, but there is still a lot of room for improvement in view of the ever-growing demand for battery performance. Therefore, how to improve the coating modification method to further enhance the electrochemical performance of the positive electrode material is a hot issue that technicians need to solve urgently. Summary of the invention
[0006] In order to further improve the electrochemical performance of Li[Ni-Co-Mn]O2 ternary positive electrode material, the present application provides a lithium-rich positive electrode material and a preparation method and application thereof.
[0007] In the first aspect, the present application provides a method for preparing a modified composite ternary positive electrode material, using the following technical solution:
[0008] A method for preparing a lithium-rich positive electrode material comprises the following steps:
[0009] 1) Prepare a mixed solution with nickel sulfate, cobalt sulfate and manganese sulfate, then add an appropriate amount of complexing agent and mix evenly to obtain a pre-liquid, then add the pre-liquid and precipitant into the reactor, and react under nitrogen protection to synthesize Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors are mixed evenly, sintered and ground to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material;
[0010] 2) Using WO3 as a substrate, Mo(CO)6 as a molybdenum source, and O3 as an oxygen source, an ALD process is used to atomically deposit Mo on the molybdenum oxide substrate to obtain a deposited material; polyethylene glycol, alkyl quaternary ammonium base, dimethyl sulfoxide, and cellulose are uniformly mixed to obtain an intermediate solution;
[0011] 3) Add the intermediate liquid, sediment and Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material is homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It is then sintered in a tubular furnace under a nitrogen atmosphere and ground to obtain a lithium-rich positive electrode material.
[0012] Preferably, in step 1), the complexing agent includes hydroxyproline and sodium lactate.
[0013] Preferably, in step 1), lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The molar ratio of the precursors is (1.25-1.3):1.
[0014] Preferably, in step 1), the sintering is first performed at a temperature of 450-550° C. for 5-6 hours, and then at a temperature of 900-980° C. for 10-15 hours.
[0015] Preferably, in step 2), the molar ratio of W to Mo in the deposited material is controlled within the range of 1:(0.7-0.85).
[0016] Preferably, in step 3), the deposited material accounts for Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]1.5-2.5wt% of the mass of O2 positive electrode material.
[0017] Preferably, in step 2), the molecular weight of the polyethylene glycol is 600-2000.
[0018] Preferably, in step 2), the alkyl quaternary ammonium base is one or more of tetramethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide.
[0019] Preferably, in step 2), cellulose accounts for 0.03-0.05 wt% of the mass of the intermediate liquid.
[0020] In a second aspect, the present application provides a lithium-rich positive electrode material, which is prepared using the above-mentioned preparation method.
[0021] In a third aspect, the present application provides an application of a lithium-rich positive electrode material, wherein the lithium-rich positive electrode material is used in the preparation of a lithium-ion battery.
[0022] In summary, this application has the following beneficial effects:
[0023] 1. This application adopts the co-deposition method to prepare the ternary positive electrode material, and regulates the ratio of various elements and the lithium content. The positive electrode material prepared by sintering has a good layered structure and a low degree of cation mixing. In addition, excess lithium can replace other metal ion positions in the transition metal layer, so that the structural stability of the material is higher. In addition, the ALD process is used to deposit and embed Mo atoms on the WO3 substrate. While introducing more oxygen vacancies, the modification effect of W and Mo atoms can effectively inhibit the occurrence of electrolyte side reactions, reduce the impedance of the battery, greatly improve the rate performance of the positive electrode material, and improve the electrochemical performance of the material. Moreover, since there is a microscopic distance between the position of the deposited and embedded Mo atoms and the position of the original W atoms, this microscopic interatomic distance can cause a spatial separation synergy between W and Mo atoms, thereby enhancing the oxygen vacancy effect, ensuring that in the subsequent discharge process, a sufficient amount of lithium ions can return to the positive electrode material, further improving the electrochemical performance of the material.
[0024] 2. In this application, polyethylene glycol, alkyl quaternary ammonium base, dimethyl sulfoxide and cellulose are used to prepare an intermediate solution, and then the sediment material and Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material is added to the intermediate solution, and under the molecular embedding and intercalation of polyethylene glycol, the deposited material and Li[Li 0.2 Ni0.6 Co 0.15 Mn 0.15 ]O2 positive electrode materials form a doping system, and a small amount of cellulose is dissolved by the alkyl quaternary ammonium base, which can form a heterogeneous dissolution system in the intermediate solution, and then cooperate with the doping system. After subsequent replacement and sintering, the sedimentary material is 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]A uniform coating layer is formed on the surface of the O2 positive electrode material. On the other hand, after the high-temperature cracking and carbonization of trace cellulose, a trace amount of carbon doping coating will be formed in the ternary material, which can further reduce the charge transfer resistance of the positive electrode material during the charging and discharging process. In addition, the multiple modification effects of the sedimentary material and trace carbon can obtain a very good composite effect and improve the electrochemical properties of the positive electrode material.
[0025] 3. The lithium-rich positive electrode material prepared by the preparation method of the present application has excellent rate performance and cycle performance, and can be used in lithium-ion batteries to improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Example 1 of the present application.
[0027] Figure 2 This is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Example 2 of the present application.
[0028] Figure 3 This is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Example 3 of the present application.
[0029] Figure 4 It is a schematic diagram of the rate performance of the lithium-rich positive electrode material of comparative example 1 of the present application.
[0030] Figure 5 It is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0033] Example 1
[0034] The method for preparing the lithium-rich positive electrode material of this embodiment comprises the following steps:
[0035] 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.25:1, sintered at 550°C for 5 h, then sintered at 900°C for 15 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 cathode material;
[0036] 2) Use WO3 with a purity of more than 99% as a substrate, clean the surface with hydrogen fluoride and deionized water before use to remove surface impurities; use high-purity Mo(CO)6 as a molybdenum source and high-purity O3 as an oxygen source, and use the ALD process to atomically deposit Mo on the molybdenum oxide substrate to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first open the molybdenum source valve to introduce the molybdenum source for 5s, then open the oxygen source valve to introduce the oxygen source for 5s, then deposit and react for 60s, and finally open the vacuum valve to remove the residual substances;
[0037] 20 mL of polyethylene glycol, 60 mL of alkyl quaternary ammonium base, 120 mL of dimethyl sulfoxide, and 0.06 g of cellulose were mixed uniformly to prepare an intermediate solution;
[0038] 3) Add 500 mL of intermediate solution, 1.5 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material was homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It was then sintered at 500°C for 6h in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material was obtained after grinding.
[0039] The complexing agent is sodium lactate solution with a concentration of 2 mol / L. The precipitating agent is sodium hydroxide solution with a concentration of 4 mol / L. The molecular weight of polyethylene glycol is 600. The alkyl quaternary ammonium base is tetramethylammonium hydroxide with a mass concentration of 40%. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.7-0.75).
[0040] The lithium-rich positive electrode material of this embodiment is prepared by the above-mentioned preparation method.
[0041] The application of the lithium-rich positive electrode material of this embodiment is to use the lithium-rich positive electrode material for preparing the positive electrode of a lithium-ion battery.
[0042] Example 2
[0043] The method for preparing the lithium-rich positive electrode material of this embodiment comprises the following steps:
[0044] 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.3:1, sintered at 450°C for 6 h, then sintered at 980°C for 10 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 cathode material;
[0045] 2) Use WO3 with a purity of more than 99% as a substrate, clean the surface with hydrogen fluoride and deionized water before use to remove surface impurities; use high-purity Mo(CO)6 as a molybdenum source and high-purity O3 as an oxygen source, and use the ALD process to atomically deposit Mo on the molybdenum oxide substrate to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first open the molybdenum source valve to introduce the molybdenum source for 5.5s, then open the oxygen source valve to introduce the oxygen source for 6s, then deposit and react for 70s, and finally open the vacuum valve to remove the residual substances;
[0046] 20 mL of polyethylene glycol, 60 mL of alkyl quaternary ammonium base, 120 mL of dimethyl sulfoxide, and 0.1 g of cellulose were mixed uniformly to prepare an intermediate solution;
[0047] 3) Add 500 mL of intermediate solution, 2.5 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material was homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It was then sintered at 500°C for 6h in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material was obtained after grinding.
[0048] The complexing agent is a mixed solution of sodium lactate and hydroxyproline, the concentration of sodium lactate is 2 mol / L, and the concentration of hydroxyproline is 0.5 mol / L. The precipitant is a sodium hydroxide solution with a concentration of 4 mol / L. The molecular weight of polyethylene glycol is 2000. The alkyl quaternary ammonium base is tetrapropylammonium hydroxide with a mass concentration of 40%. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.8-0.85).
[0049] The lithium-rich positive electrode material of this embodiment is prepared by the above-mentioned preparation method.
[0050] The application of the lithium-rich positive electrode material of this embodiment is to use the lithium-rich positive electrode material for preparing the positive electrode of a lithium-ion battery.
[0051] Example 3
[0052] The method for preparing the lithium-rich positive electrode material of this embodiment comprises the following steps:
[0053] 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH)1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.265:1, sintered at 500°C for 5 h, then sintered at 950°C for 12 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material;
[0054] 2) Use WO3 with a purity of more than 99% as a substrate, clean the surface with hydrogen fluoride and deionized water before use to remove surface impurities; use high-purity Mo(CO)6 as a molybdenum source and high-purity O3 as an oxygen source, and use the ALD process to atomically deposit Mo on the molybdenum oxide substrate to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first open the molybdenum source valve to introduce the molybdenum source for 5.5s, then open the oxygen source valve to introduce the oxygen source for 5s, then deposit and react for 65s, and finally open the vacuum valve to remove the residual substances;
[0055] 20 mL of polyethylene glycol, 60 mL of alkyl quaternary ammonium base, 120 mL of dimethyl sulfoxide, and 0.08 g of cellulose were mixed uniformly to prepare an intermediate solution;
[0056] 3) Add 500 mL of intermediate solution, 2 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material was homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It was then sintered at 500°C for 6h in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material was obtained after grinding.
[0057] The complexing agent is a mixed solution of sodium lactate and hydroxyproline, the concentration of sodium lactate is 2 mol / L, and the concentration of hydroxyproline is 0.5 mol / L. The precipitant is a sodium hydroxide solution with a concentration of 4 mol / L. The molecular weight of polyethylene glycol is 800. The alkyl quaternary ammonium base is tetrabutylammonium hydroxide with a mass concentration of 40%. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.75-0.82).
[0058] The lithium-rich positive electrode material of this embodiment is prepared by the above-mentioned preparation method.
[0059] The application of the lithium-rich positive electrode material of this embodiment is to use the lithium-rich positive electrode material for preparing the positive electrode of a lithium-ion battery.
[0060] Comparative Example 1
[0061] The preparation method of the lithium-rich positive electrode material of this comparative example comprises the following steps:
[0062] 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.25:1, sintered at 550°C for 5 h, then sintered at 900°C for 15 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 cathode material;
[0063] 2) Add 500 mL of deionized water, 1.5 g of aluminum hydroxide and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15]O2 positive electrode material, add ammonia water to control the pH value to about 9, evaporate excess water after reaction under nitrogen protection, then vacuum dry, then sinter at 500°C for 6h in a tubular furnace under nitrogen atmosphere, and obtain lithium-rich positive electrode material after grinding.
[0064] The complexing agent is sodium lactate solution with a concentration of 2 mol / L, and the precipitating agent is sodium hydroxide solution with a concentration of 4 mol / L.
[0065] The lithium-rich positive electrode material of this comparative example is prepared by the above-mentioned preparation method.
[0066] The application of the lithium-rich positive electrode material of this comparative example is to use the lithium-rich positive electrode material for the preparation of the positive electrode of a lithium-ion battery.
[0067] Comparative Example 2
[0068] The preparation method of the lithium-rich positive electrode material of this comparative example comprises the following steps:
[0069] 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.25:1, sintered at 550°C for 5 h, then sintered at 900°C for 15 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 cathode material;
[0070] 2) Use WO3 with a purity of more than 99% as a substrate, clean the surface with hydrogen fluoride and deionized water before use to remove surface impurities; use high-purity Mo(CO)6 as a molybdenum source and high-purity O3 as an oxygen source, and use the ALD process to atomically deposit Mo on the molybdenum oxide substrate to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first open the molybdenum source valve to introduce the molybdenum source for 5s, then open the oxygen source valve to introduce the oxygen source for 5s, then deposit and react for 60s, and finally open the vacuum valve to remove the residual substances;
[0071] 3) Add 500 mL of deionized water, 1.5 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material was homogenized under nitrogen protection and then vacuum dried, then sintered at 500°C for 6h in a tubular furnace under a nitrogen atmosphere, and then ground to obtain a lithium-rich positive electrode material.
[0072] The complexing agent is a sodium lactate solution with a concentration of 2 mol / L. The precipitating agent is a sodium hydroxide solution with a concentration of 4 mol / L. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.7-0.75).
[0073] The lithium-rich positive electrode material of this comparative example is prepared by the above-mentioned preparation method.
[0074] The application of the lithium-rich positive electrode material of this comparative example is to use the lithium-rich positive electrode material for the preparation of the positive electrode of a lithium-ion battery.
[0075] Performance testing
[0076] Battery assembly: The lithium-rich positive electrode materials, acetylene carbon black, and PVDF of Examples 1-3 and Comparative Examples 1-2 were mixed uniformly in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone was added and stirred to form a slurry, which was then coated on an aluminum foil and vacuum dried and cut into φ12mm positive electrode sample pieces. Then, a lithium sheet was used as the negative electrode, and a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate was used as the electrolyte. The button cells were assembled in a glove box and placed on an electrochemical tester for electrochemical performance testing. The test results are shown in Tables 1 and Figure 1-5 shown.
[0077] Table 1 Electrochemical performance test results of the first charge and discharge of the lithium-rich positive electrode materials of Examples 1-3 and Comparative Examples 1-2 at a current density of 20 mA / g
[0078]
[0079] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Table 1 and Figure 1-5 It can be seen that the lithium-rich positive electrode material of the present application has a higher charge and discharge specific capacity and a very good rate performance. Compared with traditional metal oxide coating materials, it can further improve the electrochemical performance of the battery.
[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a lithium-rich positive electrode material, characterized in that: The steps include: 1) Prepare a mixed solution with nickel sulfate, cobalt sulfate and manganese sulfate, then add an appropriate amount of complexing agent and mix evenly to obtain a pre-liquid, then add the pre-liquid and precipitant into the reactor, and react under nitrogen protection to synthesize Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors are mixed evenly, sintered and ground to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 cathode material; 2) Using WO3 as a substrate, Mo(CO)6 as a molybdenum source, and O3 as an oxygen source, an ALD process is used to atomically deposit Mo on a molybdenum oxide substrate to obtain a deposited material; polyethylene glycol, an alkyl quaternary ammonium base, dimethyl sulfoxide, and cellulose are uniformly mixed to obtain an intermediate solution; the molecular weight of the polyethylene glycol is 600-2000; the alkyl quaternary ammonium base is one or more of tetramethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide; 3) Add the intermediate liquid, sediment and Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material is homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It is then sintered in a tubular furnace under a nitrogen atmosphere and ground to obtain a lithium-rich positive electrode material.
2. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 1), the complexing agent includes hydroxyproline and sodium lactate.
3. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 1), lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The molar ratio of the precursors is (1.25-1.3):
1.
4. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 1), the sintering is first performed at a temperature of 450-550° C. for 5-6 hours, and then at a temperature of 900-980° C. for 10-15 hours.
5. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 2), the molar ratio of W to Mo in the deposited material is controlled to be in the range of 1:(0.7-0.85).
6. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In step 3), the deposited material accounts for Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]1.5-2.5wt% of the mass of O2 positive electrode material.
7. A lithium-rich positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 6.
8. An application of a lithium-rich positive electrode material, characterized in that: The lithium-rich positive electrode material prepared by the preparation method according to any one of claims 1 to 6 or the lithium-rich positive electrode material according to claim 7 is used for preparing a lithium-ion battery.
Citation Information
Patent Citations
Controllable pH value -based preparation method for lithium ion battery positive electrode material
CN106935847A
Lithium supplement material and preparation method thereof, positive electrode and secondary battery
CN116525976A